Towards Integrated Fire Management: Strengthening Forest Fire Legislation and Policies in the Andean Community of Nations - Liliana Correa-Quezada; Víctor Carrión-Correa; Carolina López; Daniel Segura; Vinicio Carrión-Paladines (Fire)
This study analyzes forest fire legislation and policies in the Andean Community of Nations (ACN)—Colombia, Ecuador, Peru, and Bolivia—focusing on prevention and control. Using a comparative law approach, similarities, differences, and implementation challenges were identified. Ecuador and Peru have more comprehensive legal structures, while Colombia’s is simpler, and Bolivia falls in between. To address these gaps, this study proposes an Andean Directive for Integrated Fire Management (ADIFM) to harmonize policies and incorporate fire ecology, ancestral knowledge, education, monitoring technologies, and post-fire restoration. This regulatory framework, tailored to Andean ecological and sociocultural conditions, would optimize fire management and strengthen ecosystem resilience. Additionally, harmonizing sanctions and regulations at the regional level would ensure more coherent and effective governance. The ADIFM would provide strategic guidance for policymakers, fostering sustainable fire management and environmental restoration across Andean ecosystems.